PENGEMBANGAN APLIKASI QnA UNTUK PENDAFTARAN MAHASISWA BARU STMIK AKAKOM - Muhammad Agung Nugroho; Ariesta Damayanti; Muhammad Fahrur Rifai; Syamsu Windarti (Journal of Information System Management (JOISM), 2021)
STMIK AKAKOM annually opens new student registration through offline and online media. Through online media, several media such as websites, social media and email are used. However, on media such as social media, there are questions that often arise regarding new student registration information. With limited human resources to always be online for 24 hours, an alternative model is needed to provide answers to these questions, even though the social media manager offline. Nowadays. In the term of technological developments, it is possible to create a model of knowledge base in the form of a summary of questions and answers to certain topics. This knowledge base can use as a model for creating a prototype application that can provide answers if there are questions related to new student registration. This study aims to provide convenience in the question and answer process by using a Google Dialogflow.